Rapid HPLC Method to Evaluate the Effect of Herbal Cream on Collagen Content of Skin Tissues Submitted to UV-B Radiation - K. Mishra, Arun; Mishra, Amrita; Verma, Anurag; Chattopadhyay, Pronobesh (Asian Journal of Chemistry, 2013)
For collagen content estimation, from skin tissue of albino rats (n = 6), treated with Calendula essential oil based cream and irradiated with UV-B rays (500 mJ/cm2, 12 min/day for one month), a simple and rapid high-performance liquid chromatographic method using C18 column and hydroxyproline as marker, was developed. The mobile phase consist of acetonitrile and 50 mM sodium acetate buffer pH 6 (15:85 v/v) and was pumped at 1.0 mL/min at 37 ºC. Cysteic acid used as an internal standard. The detection was carried out at 355 nm and the calibration curve was linear in the range of 10-100 μg/mL. The retention time of hydroxyproline was found to be 5.2 min with a total run time of 10 min. The limit of detection was 0.081 μg/mL and mean recovery was 98 % and 101 %. The intraday and interday variation was found to be less than 2 % showing high precision of the assay method. This method is rapid as the total run time is short compared to the run time of 17-30 min as reported by earlier workers. Therefore, the present method constitute a rapid and accurate diagnostic technique used for detection of hydroxyproline from UV-B irradiated skin tissue.